(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
This research is language style used in Just Alvin, Mata Najwa and Hitam Putih talk show. This research was conducted by qualitative descriptive being purposeful to analyze and describe the classification of language style found in Just Alvin, Mata Najwa and Hitam Putih talk show. The data of this research is dialogues used by host and interviewee. The data are gathered by download the video tape from YouTube, these data had been transcribed into written text. It is done to identify, categorize and analyze the dialogues of host and interviewee in the talk show into the five classification of language style. It is found that 1) there are three language style found in this research namely formal style, casual style and intimate style. 2) formal style is the most dominant style used by the host while casual style is the most dominant style used by the interviewee. 3) a. Formal style is used by the host dominantly because they are on the context of news station. b. Casual style is used by the interviewee dominantly because the questions given about their life emerge sharing moment context